2015
DOI: 10.1136/bmjspcare-2014-000793
|View full text |Cite
|
Sign up to set email alerts
|

Preferred and actual place of death in haematological malignancy

Abstract: ObjectivesHome is considered the preferred place of death for many, but patients with haematological malignancies (leukaemias, lymphomas and myeloma) die in hospital more often than those with other cancers and the reasons for this are not wholly understood. We examined preferred and actual place of death among people with these diseases.MethodsThe study is embedded within an established population-based cohort of patients with haematological malignancies. All patients diagnosed at two of the largest hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 44 publications
8
61
2
1
Order By: Relevance
“…Methods | From September 16, 2014, through January 21, 2015, we conducted a postal survey of US hematologists who provide direct care for adult patients with hematologic cancers, whom we identified from the clinical directory of the American Society of Hematology. We developed the survey instrument through a synthesis of preliminary data from a series of focus groups with hematologic oncologists, 2 a review of the relevant literature, previously published survey instruments, [3][4][5] and formal cognitive debriefing.…”
Section: Timeliness Of End-of-life Discussion For Blood Cancers: a Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods | From September 16, 2014, through January 21, 2015, we conducted a postal survey of US hematologists who provide direct care for adult patients with hematologic cancers, whom we identified from the clinical directory of the American Society of Hematology. We developed the survey instrument through a synthesis of preliminary data from a series of focus groups with hematologic oncologists, 2 a review of the relevant literature, previously published survey instruments, [3][4][5] and formal cognitive debriefing.…”
Section: Timeliness Of End-of-life Discussion For Blood Cancers: a Nmentioning
confidence: 99%
“…However, the findings are in line with surveys of program directors, medical students, and residents who all noted missed opportunities for faculty to model these skills. 4 How might educators change the culture of rounds from rewarding meticulousness to celebrating moderation? Just as we challenge trainees to explain their diagnostic reasoning, so too should we probe them to justify their use of tests and resources.…”
mentioning
confidence: 99%
“…Only 40.5% of patients (15/37) died in hospital, mainly due to inadequate family environment or a specific caregiver or patient request. (18) Data not available, n (%) 0/37 (0) 2/17 (11) We analysed the place of death of the 17 patients with AL assisted at home in our province from 01 July 2009 to 01 July 2012.…”
Section: Re Sultsmentioning
confidence: 99%
“…Moreover, many studies have reported that, given a choice, most people would prefer to die at home . It is well known that patients with haematological malignancies are more likely to die in hospital than those with other cancers or non‐malignant conditions . Physicians should pay greater attention to the patients’ perspective on time spent in hospital, and on the medical care, they receive throughout their illness and at the end of life …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation